Vertically-oriented graphene-boron nitride skeletons using graphene oxide as inorganic adhesives for high-efficiency thermal conduction of polymeric composites with electrical insulation and compressibility. (1st March 2023) - Zhang, Jiangang; Wang, Han; Zhang, Tengxin; Sun, Xinyang; Meng, Yu; Ma, Chaoqun; Zhang, Tianyu; Lu, Ni; Liu, Chang; Zeng, You
Abstract: Polymer-based thermal interface materials (TIMs) with high thermal conductivity are in high demand for rapid heat transfer between electronic components. It is still challenging to achieve significant enhancement in thermal conductivity of polymeric composites while maintaining satisfactory electrical insulation and good compressibility. In this work, we have developed a vertically-oriented graphene-boron nitride (GNP-BN) skeleton using graphene oxide (GO) as inorganic adhesives through ice-templating method, and vacuum-infiltrated with polydimethylsiloxane (PDMS) to fabricate GNP-BN/PDMS composites. The 5.2 wt% GNP-BN/PDMS composites exhibited high-efficiency thermal conduction (through-plane thermal conductivity of 1.16 W m −1  K −1 and enhancement efficiency as high as 104.7%), satisfactory electrical insulation (volume resistivity of over 10 8  Ω cm), and good compressibility (compressive modulus as low as 1.47 MPa). Such high performance is mainly attributed to the high-efficiency heat transfer pathway, low interfacial thermal resistance between components, effective hindrance to long-distance electron transport, and easy deformation of porous skeletons. The GNP-BN/PDMS composites show great potential to be used as high-performance TIMs in the field of electronic devices. Graphical abstract: Image 1 Highlights: GO were used as inorganic adhesives to effectively bridge GNP and BN together. Low interfacial thermal resistance due to phonon spectra matching between components. Thermal conductivity enhancement efficiency of the composites was as high as 104.7%. The composites exhibited satisfactory electrical insulation and good compressibility.